THE EFFECT OF FOLIC ACID SUPPLEMENTATION DURING EARLY PREGNANCY ON OROFACIAL CLEFT AMONG CHILDREN 6-24 MONTHS IN KUPANG CITY - Weraman, Pius; Haryadi, Amelia Manuel (Perhimpunan Ahli Epidemiologi Indonesia, 2022)
Orofacial cleft (OFC) is one of the most common congenital malformations in the world and Indonesia. The causes of OFC are complex, including both intrinsic (genetic) and extrinsic (environmental and behavioral) risk factors. Some studies found that there was an association between folic acid supplementation and the risk of OFC. However, studies on the effect of folic acid supplementation for OFC in Indonesia are lacking. This study aims to analyze the association of folic acid supplementation during early pregnancy with an orofacial cleft in children in Kupang City. The study was a retrospective case-control study was carried out, with a multistage sampling method including 57 participants. We examined the risk of OFC with folic acid supplementation during early pregnancy. Chi-square analysis was used in the study. The results showed that there was a significant association between folic acid use during early pregnancy and the incidence of OFC with a p-value = 0.000 (OR=20,0). Folic acid supplementation during early pregnancy can reduce the risk of OFC in children.